2016
DOI: 10.2514/1.g001382
|View full text |Cite
|
Sign up to set email alerts
|

Collision Probability Due to Space Debris Clouds Through a Continuum Approach

Abstract: As the debris population increases, the probability of collisions in space grows. Due to the high level of released energy, even collisions with small objects may produce thousands of fragments. Propagating the trajectories of all the objects produced by a breakup could be computationally expensive. Therefore, in this work debris clouds are modeled as a uid, whose spatial density varies with time under the eect of atmospheric drag. By introducing some simplifying assumptions, such as an exponential model of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…For non-equatorial orbits β max is set equal to the inclination where the fragmentation occurred i F if i F ≤ π/2 and equal to π −i f otherwise (Letizia et al, 2015c).…”
Section: Continuity Equationmentioning
confidence: 99%
“…For non-equatorial orbits β max is set equal to the inclination where the fragmentation occurred i F if i F ≤ π/2 and equal to π −i f otherwise (Letizia et al, 2015c).…”
Section: Continuity Equationmentioning
confidence: 99%
“…Therefore, it can be applied to study many different scenarios of collisions to understand, for example, which objects, in case of fragmentation, are more likely to have a large impact on the global collision risk for operational satellites (Letizia et al, 2015b). This was done by applying the proposed method to compute a grid of fictitious breakups, store the scenario evolution, and evaluate their effect on several targets without having to simulate the fragmentations for each target spacecraft.…”
Section: Continuity Equation Methods For Fragmentation Modellingmentioning
confidence: 99%
“…The method, summarised in Section 2, is able to model the evolution of debris clouds including all the small fragments down to 1 mm in size, with a reduced computational effort compared to the propagation of the individual trajectories. This enabled to perform an extended analysis on the contribution of small fragments to the collision probability (Letizia et al, 2015b), proving that the method can be useful to evaluate the hazard posed by small fragments to operational spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…Kurihara et al (2015) investigated the impact frequency calculated by the debris environment model and the impact craters on the surface of the exposed instrument of the Tanpopo mission; they suggested that the impact energy is in proportion to the crater volume, and is not related to the projectile materials and relative speed. Letizia et al (2016) modeled the debris clouds as a uid with the density changed under the force caused by the atmospheric drag, they derived the analytical expression for the density evolution of the uid, and the method can be applied for the simulation of several collision scenarios in a short time. Francesconi et al (2015) used the honeycomb sandwich panels to model the structure of the spacecraft and presented an engineering model describing debris clouds.…”
Section: Introductionmentioning
confidence: 99%